(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines technological literacy as a key component of digital culture and its impact on the formation of professional competencies of future teachers. Possible ways of integrating digital technologies into educational practice are considered. The main focus is on the definition of technological literacy as the ability to effectively and responsibly use modern digital technologies in educational and professional activities. The study identifies cultural differences in the perception of technology and their impact on technological literacy, emphasizing the importance of cultural context in education. The article emphasizes the importance of the cultural context in the formation of technological literacy and demonstrates that a positive perception of technology contributes to their effective integration into education and professional activities of future teachers. Technological literacy also involves understanding how technologies are created and developed. This knowledge includes the basic principles of various technologies, their development and implementation processes, as well as innovative approaches and methodologies. An important aspect of technological literacy is awareness of how technology affects society. This includes understanding the social, economic and cultural implications of the introduction of new technologies. A technologically literate person should be able to assess these consequences and make informed decisions in their professional and personal lives.